Interspecific differences in the response of autotrophic microorganisms to atrazine and S-metolachlor exposure - Laura Malbezin; Nicolas Mazzella; Sébastien Boutry; Isabelle Lavoie; Soizic Morin (Ecotoxicology and Environmental Safety)
Atrazine and S-metolachlor are herbicides widely used on corn and soybean crops where they are sometimes found in concentrations of concern in nearby aquatic ecosystems, potentially affecting autotrophic organisms. The aim of this study was to investigate the response of the green algae Enallax costatus, the diatom Gomphonema parvulum and a culture of the cyanobacteria Phormidium sp. and Microcystis aeruginosa, to atrazine and S-metolachlor alone and in mixture (0, 10, 100 and 1000 µg.L−1, for 7 days). For each culture, chlorophyll fluorescence and effective quantum yield of photosynthesis were determined and compared with lipid and methyl-ester fatty acid profiles. In general, the green algae was most strongly affected by atrazine and S-metolachlor. In particular, atrazine led to a total inhibition of photosynthesis and a sharp decrease in triacylglycerols (TAGs), while S-metolachlor caused a partial decrease in photosynthesis in the green algae and a sharp increase in reserve lipids in the diatom when the herbicide was in mixture. The effect of the mixture of compounds depended on the descriptor considered. Indeed, atrazine seemed to explain the toxicity of the mixture for photosynthetic parameters, while certain lipid classes showed intermediate responses between compounds. The results suggest mechanisms of shade adaptation, algal population increase and lipid remodeling in response to compound exposure. The results reveal differences in sensitivity between species after 7 days exposure to the two compounds alone and in mixture. These results support the value of using the study of lipid and fatty acid profiles as complementary information to traditional descriptors for the assessment of pesticide exposure on photoautotrophic organisms.